2013
DOI: 10.4142/jvs.2013.14.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilarity ofccrABgene sequences between methicillin-resistantStaphylococcus epidermidisand methicillin-resistantStaphylococcus aureusamong bovine isolates in Korea

Abstract: The sequences of the ccrAB genes from bovine-, canine- and chicken-originating methicillin-resistant Staphylococcus (S.) epidermidis (MRSE) and bovine methicillin-resistant Staphylococcus (S.) aureus (MRSA) were compared to investigate the frequency of intra-species horizontal transfer of the staphylococcal cassette chromosome mec (SCCmec) complex. Nineteen MRSE strains were isolated from bovine milk, chickens, and dogs, and their genetic characteristics were investigated by multilocus sequence typing and SCCm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
1
7
0
4
Order By: Relevance
“…SCCmec type IV, carried by most MRSE isolates identified in the present study, has been reported to be the most frequent type of MRSE in animals (Park et al, 2013) and humans (Miragaia et al, 2008;Barbier et al, 2010). The other SCCmec types (V and NT) have been described in MRSE isolates from infections of companion animals (Kern and Perreten, 2013), in ovine mastitis (Onni et al, 2011) and healthy cattle .…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…SCCmec type IV, carried by most MRSE isolates identified in the present study, has been reported to be the most frequent type of MRSE in animals (Park et al, 2013) and humans (Miragaia et al, 2008;Barbier et al, 2010). The other SCCmec types (V and NT) have been described in MRSE isolates from infections of companion animals (Kern and Perreten, 2013), in ovine mastitis (Onni et al, 2011) and healthy cattle .…”
Section: Discussionmentioning
confidence: 70%
“…The predominance, widespread distribution and diversity of SCCmec in S. epidermidis suggest that this bacterial species might be a potential reservoir of this cassette for S. aureus or other staphylococci. However, recent research has suggested that intra-species transfer of the SCCmec complex between S. aureus and S. epidermidis is not a frequent event, at least in cattle (Park et al, 2013). The role of S. epidermidis in pigs as a SCCmec reservoir for S. aureus should be further investigated.…”
Section: Discussionmentioning
confidence: 98%
“…Lack of robust concordance was observed between results obtained by both schemes, with guidelines from Kondo et al (2007) showing a remarkable high diversity index (SID 0.89 versus 0.71), and reflecting the high intergenic diversity within MRCoNS cassettes. SCC mec IV was the predominant typeable cassette for both owner and pets, and despite, additional cassettes have been sporadically detected, it is also the most prevalent cassette among humans and companion animals (Ruppe et al, 2009; Barbier et al, 2010; Lebeaux et al, 2012; Aslantas et al, 2013; Kern and Perreten, 2013; Park et al, 2013; Weiss et al, 2013; Becker et al, 2014; Abadi et al, 2015; McManus et al, 2015; Couto et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As shown [158], there is much more variation in the sequences, and ideally the SCCmec types should be subdivided based on differences in sequences. This task has become feasible with new-generation sequencing; therefore, it no longer will be a great challenge to develop a more detailed subtyping scheme of SCCmec types to enable researchers to follow their movements, plasticity, and epidemiology.…”
Section: Methicillin Resistance In Staphylococcimentioning
confidence: 99%